PENINGKATAN KERJASAMA DAN HASIL BELAJAR TEMATIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Naila Filahatin Ajria; Bambang Ismanto; Firosalia Kristin (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2018)
This research aims to: (1) to increase cooperation and thematic learning outcomes (knowledge, attitudes, and skills) grade IV SDN Blotongan 02 learning through Problem Based Learning; and (2) to describe the increase in cooperation and thematic learning outcomes (knowledge, attitudes, and skills) grade IV SDN Blotongan 02 learning through Problem Based Learning.. The type of research used is classroom action research with research subjects, namely fourth grade students of Blotongan 02 State Elementary School, totaling 34 students. Data collection techniques include observation, documentation, and written tests. Data analysis in this study uses the descriptive analysis of the qualitative and quantitative comparative analysis. On condition of prasiklus, the cooperation of students not yet optimal. After research, obtained the cooperation activities of students in cycle I, from 34 students there were 8 students (23.53%) reach the predicate "very good", 18 students (52.94%) with the predicate "very good", 6 students (17.65%) with the predicate "good enough", and there are still 2 students (5.88%) with the predicate "less good". In cycle II, there are 17 students (50.00%) reach the predicate "very good", 12 students (35.29%) with the predicate "very good", 5 students (14.71%) with the predicate "good enough", and 0.00% of students with "less good". In addition, based on the research data were also obtained the thematic learning outcomes of students on the Indonesian language cycle I (70.59%) cycle II (85.29%), science cycle I (64.71%) cycle II (76.47%), IPS cycle I (73.53%) cycle II (88.241%). Based on the results of the study it can be concluded that there is an increase in cooperation and student thematic learning outcomes through the problem based learning model.